Esthesioneuroblastoma, Neuroendocrine Carcinoma, and Sinonasal Undifferentiated Carcinoma: Differentiation in Diagnosis and Treatment - Su, Shirley Y.; Bell, Diana; Hanna, Ehab Y. (International Archives of Otorhinolaryngology, 2014)
Introduction Malignant sinonasal tumors comprise less than 1% of all neoplasms. A wide variety of tumors occurring primarily in this site can present with an undifferentiated or poorly differentiated morphology. Among them are esthesioneuroblastomas, sinonasal undifferentiated carcinomas, and neuroendocrine carcinomas.Objectives We will discuss diagnostic strategies, recent advances in immunohistochemistry and molecular diagnosis, and treatment strategies.Data Synthesis These lesions are diagnostically challenging, and up to 30% of sinonasal malignancies referred to the University of Texas MD Anderson Cancer Center are given a different diagnosis on review of pathology. Correct classification is vital, as these tumors are significantly different in biological behavior and response to treatment. The past decade has witnessed advances in diagnosis and therapeutic modalities leading to improvements in survival. However, the optimal treatment for esthesioneuroblastoma, sinonasal undifferentiated carcinoma, and neuroendocrine carcinoma remain debated. We discuss advances in immunohistochemistry and molecular diagnosis, diagnostic strategies, and treatment selection.Conclusions There are significant differences in prognosis and treatment for esthesioneuroblastoma, neuroendocrine carcinoma, and sinonasal undifferentiated carcinoma. Recent advances have the potential to improve oncologic outcomes but further investigation in needed.
Keywords: sinonasal malignancy; esthesioneuroblastoma; sinonasal undifferentiated carcinoma; neuroendocrine carcinoma; olfactory neuroblastoma